Performance Evaluation of Artificial Megneto-Dielectric Metamaterial with Microstrip Patch Antenna for Wireless System - Pinsakul, Atcharaporn; Supanakoon, Pichaya; Promwong, Sathaporn (My University, 2018)
This paper we presents the performance evaluation of artificial magneto dielectric substrate with microstrip patch antenna for wireless system. From the result, at the resonance frequency 2.45 GHz have the radiation efficiency and the real gain are 88.87% and 6.89 dBi, respectively. The microstrip patch antenna on finite artificial magneto dielectric substrate by used metamaterial structure. The unit cell consist of multi square loop pinned in the dielectric material. The feature of the antenna can be rectify with controlling permeability (boldsymbolmu-eff) and permittivity (boldsymbolvarepsilon-eff).
Keywords: component; magneto-dielectric; Metasubstrates; microstrip patch antenna